Advocating for the Digitization of the History of China-Africa Diplomatic Relations (Journal of the Digital Humanities Association of Southern Africa, 2024)
This article delves into the examination of research pertaining to the historical establishment of diplomatic relations between China and African countries, intersecting with the domain of historical digitization, focusing on the fusion of oral history and the digital preservation of historical documents. After underscoring the significance of investigating the history of the establishment of diplomatic relations between China and African nations, the study conducts a literature review, delving into the status quo of historical digitization research in both Chinese and African academies with both sides’ current study on each other’s history and Sino-African relations, thereby furnishing a robust technical and scholarly groundwork for this research. Afterward, the article deliberates upon the prospects and challenges intrinsic to digitizing the history surrounding the initiation of diplomatic relations between China and Africa. Conclusively, the article proffers recommendations aimed at catalyzing the digitization trajectory of this historical narrative, spanning two tiers, including the official multilateral cooperation mechanism and collaborative endeavors involving private academic institutions.
Keywords: China-Africa Relation; History Digitization; International Relation; Oral History